Implementasi Kebijakan Transisi Penerbitan Faktur Pajak Dari Aplikasi E-Faktur Ke Sistem Coretax di Kantor Pelayanan Pajak Pratama Jayapura - Suhely S; Westim Ratang; Risky Novan Ngutra (PT Publikasiku Academic Solution, 2026)
This research is motivated by the transition of the tax invoice issuance policy from the e-Faktur application to the Coretax system as part of the digital reform of tax administration in Indonesia. These changes not only have an impact on the technical aspect, but also on the administrative process, user experience, and quality of tax services. This study aims to analyze the implementation of Coretax and its influence on the quality of tax services at the Jayapura Pratama Tax Service Office. The method used is a qualitative approach with a case study design through data collection in the form of questionnaires and in-depth interviews. The results show that the implementation of Coretax takes place in an adaptive and non-linear manner, where the perception of system usefulness appears earlier than the ease of use. In the early stages, various technical obstacles and increased administrative burdens were found that affected the taxpayer experience. Nevertheless, the quality of tax services was maintained thanks to institutional support, although it was greatly influenced by the stability of the system. In conclusion, the success of Coretax's implementation is determined by the readiness of the system, user capacity, and organizational support in facing the digital policy transition period.